(untitled) (Vietnam Journal of Community Medicine, 2024)
Aims: 1. Symptomatic analysis and clinical subdivision of benign prostate hypogonadism (BPH) based on latent tree analysis model in 2024; 2. Initially formulate traditional medicine disease pattern diagnostic criteria for benign prostate hypogonadism based on the latent plant model. Methods: The questionnaire with 65 symptoms was used to survey 394 qualified BPH patients, disease information was processed by latent tree analysis model. Result: After modeling, 12 latent variables (from Y0 to Y11) were established, each of which represented the set of observed variables as symptoms. According to traditional medicine theories, 5 clinical disease patterns were found. Conclusions: Analysis of the latent tree model of 65 symptoms in 394 patients of CKT established 12 latent variables from Y0 to Y11, of which Y0,Y1,Y2,Y5,Y6,Y7,Y8,Y9 was the pattern of co-existing symptoms. Y10 is the model of symptoms of exclusion. 5 types of disease patterns are established: heat and dampness bladder, defficient Yang Kidney, urethral obstruction, stagnant Qi-Liver, deficient ZhongJiao; with accompanying symptoms there is a maximum CMI of 95%.